Group Guidance Using Positive Psychological Interventions to Enhance Adolescents' Gratitude - Dikdik Garnika Garnika; Feny Cholisoh (Universitas Muria Kudus, 2026)
This study aimed to examine the effectiveness of group guidance services using positive psychological interventions in enhancing adolescents gratitude. A quantitative approach was employed using a quasi-experimental method with an equivalent time series design. The study population consisted of 319 eleventh-grade students at SMK Negeri 1 Ciamis. The sample of nine students was selected using nonprobability sampling through a convenience sampling technique. Data were collected using the Indonesian version of the Gratitude Scale and analyzed through the Shapiro–Wilk normality test followed by the Wilcoxon Signed Rank test. The results indicated a significant increase in students’ gratitude after participating in group guidance using positive psychological interventions. Improvements were observed in both personal and transpersonal dimensions, with the greatest increase in positive feelings and the smallest increase in gratitude expression. This method is recommended as a guidance and counseling strategy to enhance adolescents’ gratitude within comprehensive school counseling services. This study is among the first to apply group guidance based on positive psychological interventions to enhance both personal and transpersonal gratitude among vocational high school students